Victim-Warriors and Restorers—Heroines in the Post-Apocalyptic World of Mad Max: Fury Road - Anna Reglińska-Jemioł (Lodz University Press, 2021)
The article discusses the evolving image of female characters in the Mad Max saga directed by George Miller, focusing on Furiosa’s rebellion in the last film—Mad Max: Fury Road. Interestingly, studying Miller’s post-apocalyptic action films, we can observe the evolution of this post-apocalyptic vision from the male-dominated world with civilization collapsing into chaotic violence visualized in the previous series to a more hopeful future created by women in the last part of the saga: Mad Max: Fury Road (2015). We observe female heroes: the vengeful Furiosa, the protector of oppressed girls and sex slaves, the women of the separatist clan, and the wives of the warlord, who bring down the tyranny and create a new “green place.” It is worth emphasizing that the plot casts female solidarity in the central heroic role. In fact, the Mad Max saga emerges as a piece of socially engaged cinema preoccupied with the cultural context of gender discourse. Noticeably, media commentators, scholars and activists have suggested that Fury Road is a feminist film.